Completed Family Size Of Rural Women : Changing Patterns In Four Decades Of Marriage Cohorts - Rao Sarah S; Indrayan A; Aggarwal O.P; Sethi N.K; Chuttani C.S (Wolters Kluwer Medknow Publications, 1987)
Eight hundred and sixty five ever married women of age 15 years and above belonging to two villages near Delhi were interviewed. Complete fertility history was taken. This communication is restricted to 229 women who had completed 45 years of age at the time of the study. The year of marriage has been categorized in to decades i.e. 1932 before, 1933 to 42,1943 to 52 and 1953 to 1962. Fertility profile in terms, of conceptions, live births and children living for at least five years in 4 decades of marriage cohort is provided. The data on sterilized and unsterilised couples have been separately reported. Literacy of women has been used as the background characteristic and analysis by literacy status is presented. The study demonstrates that literacy markedly brings about a decline in fertility among rural women. Even among illiterate women, general social development witnessed over the four decades has materially helped in reducing fertility. Finally, sterilization to be effective must be adopted by couples when young.